2015
DOI: 10.4174/astr.2015.88.6.318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visceral fat area on outcomes of laparoscopyassisted distal gastrectomy for gastric cancer: subgroup analysis by gender and parameters of obesity

Abstract: PurposeThe aim of this study was to investigate the impact of the visceral fat area (VFA) of patients with gastric cancer undergoing laparoscopic surgery on operative outcomes such as number of retrieved lymph nodes (LNs) and operative time.MethodsWe retrospectively reviewed the medical records and the CT scans of 597 patients with gastric cancer who underwent laparoscopy assisted distal gastrectomy (LADG) with partial omentectomy and LN dissection (>D1 plus beta). Patients were stratified by gender, VFA, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…In the past, the impact of visceral fat area on surgical outcome were well elucidated [24, 25], and some studies indicated that the larger visceral or peri-organ fat areas prolonged the operative time of laparoscopic radical nephrectomy [26], laparoscopic adrenalectomy [27], and laparoscopic radical prostatectomy [28]. In the present study, we measured the retroperitoneal fat tissue thickness using preoperative standard 2-dimensional transverse CT scan images.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the impact of visceral fat area on surgical outcome were well elucidated [24, 25], and some studies indicated that the larger visceral or peri-organ fat areas prolonged the operative time of laparoscopic radical nephrectomy [26], laparoscopic adrenalectomy [27], and laparoscopic radical prostatectomy [28]. In the present study, we measured the retroperitoneal fat tissue thickness using preoperative standard 2-dimensional transverse CT scan images.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,21 We also showed that VFA appears to be a risk factor for postoperative morbidities, intraoperative blood loss, and operation time. However, the measurement of VFA on CT requires unique software, and a more simple predictive factor is awaited that is much easier to measure and as useful as VFA.…”
Section: Discussionmentioning
confidence: 67%
“…Much of the research on surgical treatment of gastric cancer has focused on obesity in recent years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Obesity is associated with increased blood loss, a prolonged operative time, a high rate of postoperative complications, and inadequate lymph node staging.…”
Section: Introductionmentioning
confidence: 99%